Residence in Proximity of an Iron Foundry and Risk of Lung Cancer in the Municipality of Trieste, Italy, 1995–2009 - Bidoli, Ettore (Int J Environ Res Public Health, 2015)
We assessed the risk of lung cancer in people living near the iron foundry located within the city of Trieste, Northeastern Italy. Between 1995 and 2009, all incident cases of lung cancer and corresponding population were considered. A deposition model of the foundry-specific emissions of SO(2) defined: “nearby”, “urban”, and “outlying” areas. Rate ratios (RRs) and annual percent changes (APCs) were computed. Among nearby residents, significantly increased risks of lung cancer were noted in men below age 75 years (RR = 1.35 vs. urban area; 95% CI: 1.03–1.77). In women, and in men aged 75 years or older, no significant RRs were observed. Conversely, people living in the outlying area appeared to be at lower risk than residents in the urban area- in all age groups, in men (RR = 0.87; 95% CI: 0.78–0.98) and in women (RR = 0.74; 95% CI: 0.62–0.88). Negative statistically significant APC was recorded in men living in urban areas (–2.6%), whereas in women APC significantly increased among those living in the urban area (+2.3%). Multiple interpretations for this observation are plausible, since several factors might have modified and/or confounded the risk of lung cancer, including air pollution from other sources and road traffic, occupational and smoking patterns.